UMP: First to offer German-Modelled Engineering Programme - UMP, LIB
Universiti Malaysia Pahang (UMP) is, again, at the forefront when it comes to offering high quality engineering undergraduate programme – with the latest modelled after Germany’s tertiary curriculum – said the Minister of Higher Education, Dato’ Seri Mohamed Khaled Nordin, at the official opening of the University-Industry Forum 2010 recently.